Adaptive Electoral Strategies of Gerindra in the 2024 Presidential Election in Jepara, Indonesia - Tegar Muhammad Rafly; Moh. Aris Munandar (Universitas Negeri Semarang, 2025)
The 2024 Presidential Election in Indonesia revealed increasingly dynamic electoral competition shaped by interactions between national political narratives and local political contexts. In Jepara Regency, Prabowo–Gibran won the presidential election despite Gerindra not being the dominant legislative party and despite the strong electoral presence of PPP and PDI-P, creating a political anomaly that challenges conventional assumptions about party strength and presidential voting behavior. Previous studies have focused on candidate branding, digital campaigns, coalition politics, and organizational communication but have not explained electoral variation within the same party organization across different local contexts. This study analyzes Gerindra’s adaptive electoral strategy across three sub-districts with contrasting electoral outcomes in Jepara Regency. Using a qualitative comparative approach based on interviews, documentation, triangulation, and SWOT analysis, the study finds that campaign effectiveness depended on contextual adaptation integrating organizational mobilization, psychological framing, sociological networks, coalition cooperation, and local political communication. The findings contribute to the concept of adaptive electoral strategy by explaining how political organizations adjust campaign resources and communication to heterogeneous local political environments.